'Writing the rules of the global economy': how America defines the contours of international investment law. Issue 2 (9th October 2018) - Schneiderman, David
Abstract: Some have characterised the standards of protection promoted by investment treaty law as a form of 'denationalised law'. US Congressional debates over trade promotion authority suggest otherwise. This case study reveals how investment treaty standards exemplify the fictitious universalisation of the particular case, namely, protections inspired by US constitutional law. Even as international protections surpass national constitutional guarantees, the proposition that Americans should determine the content of international law could not be resisted.